The potential role of socio-hydrological models for participatory water governance in Burkina Faso - Carr, Gemma; Barendrecht, Marlies; Debevec, Liza (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Halting and reversing water quality degradation is a major global concern. The variety of needs and priorities placed on water resources make the issue of water pollution multifaceted and complex. Addressing water quality management requires an approach that can tackle the diversity of requirements and concerns to achieve effective strategies. In Burkina Faso, stakeholder participation plays an important role in effective catchment management. The Participatory Water Governance Project in Rural Burkina Faso has developed support strategies to strengthen the capacity of local-level Water User Committees. Research conducted by TU Wien (Technical University Vienna) and International Water Management Institute (IWMI) aims to support the project by exploring the potential role of socio-hydrological models in water management decision making. The areas around the River Kou and Bapla Reservoir were the focus for this part of the study. The specific question addressed by TU Wien was: can a socio-hydrological model be developed that accurately captures the relationships between people and water quality in the study area?